2006
DOI: 10.1021/jm060576k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tongs Containing Amino Acid Mimetic Fragments:  New Inhibitors of Wild-Type and Mutated HIV-1 Protease Dimerization

Abstract: We have designed, synthesized, and evaluated the inhibitory activity and metabolic stability of new peptidomimetic molecular tongs based on a naphthalene scaffold for inhibiting HIV-1 protease dimerization. Peptidomimetic motifs were inserted into one peptidic strand to make it resistant to proteolysis. The peptidic character of the molecular tongs can be decreased without changing the way they inhibit dimerization. Mutated HIV-1 proteases are also vulnerable to dimerization inhibitors, and the multimutated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 34 publications
3
50
1
Order By: Relevance
“…Hence, the inhibition of dimerization of HIV-1 protease subunits represents a unique target for potential intervention of HIV-1 replication. The strategy to target protease dimerization as a possible anti-HIV-1 modality has been explored (8,(11)(12)(13), and certain compounds have been reported as potential protease dimerization inhibitors. However, no direct evidence of dimerization inhibition by such compounds has been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the inhibition of dimerization of HIV-1 protease subunits represents a unique target for potential intervention of HIV-1 replication. The strategy to target protease dimerization as a possible anti-HIV-1 modality has been explored (8,(11)(12)(13), and certain compounds have been reported as potential protease dimerization inhibitors. However, no direct evidence of dimerization inhibition by such compounds has been documented.…”
Section: Discussionmentioning
confidence: 99%
“…There are four anti-parallel ␤-sheets involving the N and C termini of both monomer subunits and they contribute close to 75% of the dimerization energy (10), explaining at least in part why DRV failed to dissociate mature protease dimer (see below). The termini interface has been explored as a dimerization inhibition target by several groups (11)(12)(13). We have also recently reported that certain peptides containing the dimer interface sequences amino acids 1-5 and amino acids 95-99 blocked HIV-1 infectivity and replication (14).…”
mentioning
confidence: 99%
“…Compound 145 showed a dimerization inhibition K i of 0.4 µM; however, its poor water solubility limits its clinical viability. 189 Polar substituents were incorporated into this scaffold to address this issue. Compounds 146 and 147 incorporate a carbamate moiety into this scaffold.…”
Section: (5) Recent Progress Towards Hiv-1 Protease Inhibitorsmentioning
confidence: 99%
“…This approach has evolved to linking peptides with flexible alkyl tethers (Zutshi and Chmielewski, 2000) and semirigid alkyl based tethers (Ulysse and Chmielewski, 1998), which increase the distance between the peptides to approximate that of the PR termini in the dimer (~10 Å). The conformational freedom of these linked peptides was addressed by the use of pyridinediol and naphthalene based molecularly constrained scaffolds (Bouras et al 1999; Song et al 2001; Merabet et al 2004; Bannwarth et al 2006). Known as ‘molecular tongs’, these compounds are designed to position the interface peptides to clamp the termini of a PR monomer (Fig.…”
Section: Targeting the Pr Dimer Interface With Interface Peptidesmentioning
confidence: 99%
“…These studies have culminated in a set of optimised tongs with symmetrical peptidomimetic sequences based on an optimised PR C-terminal sequence. The tongs inhibit the activity of HIV-1 PR that are either sensitive or resistant to PIs with Ki values from 0.4–4.8 μM in cell free assays (Bannwarth et al 2006). …”
Section: Targeting the Pr Dimer Interface With Interface Peptidesmentioning
confidence: 99%